2007
DOI: 10.1152/jn.01169.2006
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Voltage-Sensitive Dye Imaging of Rat Cortical Activity With High Signal-to-Noise Ratio

Abstract: We describe methods to achieve high sensitivity in voltage-sensitive dye (VSD) imaging from rat barrel and visual cortices in vivo with the use of a blue dye RH1691 and a high dynamic range imaging device (photodiode array). With an improved staining protocol and an off-line procedure to remove pulsation artifact, the sensitivity of VSD recording is comparable with that of local field potential recording from the same location. With this sensitivity, one can record from approximately 500 individual detectors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
164
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(177 citation statements)
references
References 48 publications
13
164
0
Order By: Relevance
“…The spatial profile of the VSD images showed initial focal activity roughly the diameter of a barrel column (ϳ400 m) followed by a rapid horizontal spread preferentially within a whisker row and then to surrounding cortex, in agreement with previous studies (Kleinfeld and Delaney 1996;Petersen and Sakmann 2001). Similarly, in previous studies using electrophysiology and VSD imaging of barrel cortex, it was shown that responses start in layer 4 of barrels, progress vertically directly above the barrel into layer 2/3, and then spread horizontally in layer 2/3 in a "pagoda like" manner (Kleinfeld and Delaney 1996;Lippert et al 2007;Petersen and Sakmann 2001;Tanifuji et al 1994).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The spatial profile of the VSD images showed initial focal activity roughly the diameter of a barrel column (ϳ400 m) followed by a rapid horizontal spread preferentially within a whisker row and then to surrounding cortex, in agreement with previous studies (Kleinfeld and Delaney 1996;Petersen and Sakmann 2001). Similarly, in previous studies using electrophysiology and VSD imaging of barrel cortex, it was shown that responses start in layer 4 of barrels, progress vertically directly above the barrel into layer 2/3, and then spread horizontally in layer 2/3 in a "pagoda like" manner (Kleinfeld and Delaney 1996;Lippert et al 2007;Petersen and Sakmann 2001;Tanifuji et al 1994).…”
Section: Discussionsupporting
confidence: 89%
“…VSD imaging measures changes in membrane potential over large populations of neurons primarily in layer 2/3 of cortex (Civillico and Contreras 2006;Ferezou et al 2006;Jin et al 2002;Kleinfeld and Delaney 1996;Lippert et al 2007) and is thus useful for revealing the time and spread of barrel responses as well as more distant subthreshold modulatory response. Civillico and Contreras (2006) used this method to study barrel fields in mice and found, surprisingly, only suppressive effects in multiwhisker responses.…”
mentioning
confidence: 99%
“…It has been reported that optical imaging may record neuronal responses mainly from layers II and III in the cerebral cortex (Horikawa et al 1996;Lippert et al 2006), implying that synaptic plasticity may have been induced in these layers of the auditory cortex in the present study. These results correspond to reports that layers II and III of the barrel cortex play an important role in cortical plastic changes (Huang et al 1998) and that LTP can be induced in the horizontal connections in layers II and III of the motor cortex (Hess et al 1996).…”
Section: Discussionmentioning
confidence: 54%
“…Traditionally, this is called "spontaneous ongoing activity", as the sources of this activity are not known. This intrinsic activity is also communicated between cortical areas (Arieli et al, 1995;Lippert et al, 2007;Xu et al, 2007).…”
Section: Spontaneous and Intrinsic Communication Dynamics-experimentsmentioning
confidence: 99%
“…In principle, this may be possible in studies of anesthetized brains, where it is sometimes possible to capture the population of neurons bifurcating into an up-state (Figure 1). Then one can follow how the up-state spreads to populations of neurons in adjacent areas (Lilly, 1954;Lippert et al, 2007;Xu et al, 2007;Huang et al, 2010;Gao et al, 2012;Zheng and Yao, 2012). In contrast to sensory evoked activity, the spontaneous up-states may spread from different origins in the cortex.…”
Section: Spontaneous and Intrinsic Communication Dynamics-experimentsmentioning
confidence: 99%